BERBAGAI FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PELAPORAN KEUANGAN - Putri, Apriliani Issana; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to test and to prove empirically the factors i.e.: profitability, liquidity, leverage, the complexity of operating company, public ownership, the reputation of Public Accountant Office, and the substitution of auditor which have influence to the timeliness of the submission of financial statement of the manufacturing companies specifically the LQ45 companies. The result of the research shows that profitability, liquidity, leverage, public ownership, and the reputation of public accountant office have significant influence to the timeliness of the submission of financial statement. Nevertheless, No evidence has been found that the complexity of operating company and the substitution of auditor has influence to the timeliness of the submission of financial statement.Keywords: Timeliness, Financial Statement, the Complexity of Operating Company, Public Ownership, and the Reputation of Public Accountant Office.